Ethical issues in the application of artificial intelligence (AI) in academic Libraries – A study - Poologanathan, P. (Bharathidasan University, 2024)
Artificial Intelligence (AI) technology refers to the development of computer systems that can perform tasks typically requiring human intelligence, such as learning, reasoning, problem-solving, perception, and decision-making. These systems leverage techniques like machine learning, natural language processing, and computer vision to analyze data, recognize patterns, and make decisions or predictions. Al technology enables machines to continuously improve their performance through experience and adapt to new information, making it widely applicable variety of disciplines such as healthcare, finance, education, Agriculture, Smart Cities, manufacturing, and more. Its goal is to enhance efficiency, automate processes, and offer intelligent, data-driven solutions. In the high education sector, Academic libraries are specialized libraries that support the educational and research needs of institutions of higher learning, such as Universities, colleges, and research institutes. They provide a vast collection of academic resources for the facilitate study, teaching, and research. Their primary role is to support the academic goals of students, faculty, and researchers by providing relevant resources. Today, academic libraries use numerous technologies to provide the satisfactory service to their readers. Artificial intelligence (Al) technology is one of them. The application of Artificial Intelligence (AI) in academic libraries offers many benefits, such as enhanced user experience & Information Retrieval, streamlined operations, streamlined research support, learning path recommendations and data analysis capabilities. However, challenges loom large, several ethical dilemmas arise when Al is employed in academic libraries such as Bias in Al Algorithms, Privacy Concerns, transparency and accountability, intellectual Property Rights, job displacement, quality of service and human touch, data ownership and consent, access inequality and ethical Use of Al for Decision-Making. Therefore, this study mainly examines the ethical challenges associated with application of Al in academic libraries, and provides the possible suggestions for the issues.